Transient analysis of electrical drives: Applications to the permanent magnet synchronous generator - Delaleau, Emmanuel (E3S web of conferences, 2023)
This paper establishes that differential flatness , a property shared by most of the model of electrical drives, allows to perform transient analysis on the models of electrical machines, and especially electric generators which are so important in renewable energy systems (wind turbine, tidal turbine...). Transient analysis of electrical machines is indeed a difficult subject not completely solved today. The possibility to parameterize the trajectories of a system from the differential flatness property gives the possibility to perform simple transient analysis in various operation modes. The example of the Permanent Magnet Synchronous Generator (PMSG) illustrates the paper.